HAD A SOLAR POWER PLANT ANALYSED ON-GRID SYSTEM IN PALIPI VILLAGE, SAMOSIR - Solly Arya; Zulkarnain Lubis; Antoni Antoni (Sean Institute, 2022)
At this time the availability of fossil energy itself is much less available and cannot be renewed in a short period of time. Where the need for electrical energy continues to increase, which is caused by the increasing population and the increasing number of commercial building developments. Indonesia has the potential for renewable energy resources in relatively large quantities. Among these sources, where this research discusses solar energy, it is one of the unlimited energy sources and is most widely used as an energy source used to generate electricity in areas that will develop in North Sumatra.